Pemanfaatan AEOI untuk Meningkatkan Kepatuhan Wajib Pajak High Wealth Individual dalam Program Pengungkapan Sukarela - Era Widi Astuti; Yulianti Abbas (Politeknik Ganesha Medan, 2023)
Utilization of Automatic Exchange of Information (AEOI) data is expected to be able to encourage taxpayers are willing to take part in the Voluntary Disclosure Program (PPS) by disclosing assets that have never been reported in the Annual Tax Return or Tax Amnesty. This study aims to evaluate the effectiveness of AEOI in increasing High Wealth Individual (HWI) Taxpayer compliance during the PPS period at KPP X. This research is important to do because there are differences in the results between research conducted before and after the period of utilization of AEOI data by DGT starting in 2020. In addition, AEOI data, which is considered to be able to improve tax compliance, has several challenges in its utilization, namely data synchronization and rejection by taxpayers. The effectiveness of data utilization is measured using the CIPP Evaluation Model. This research is qualitative with a case study approach. Data collection was carried out through interviews with Account Representatives (AR) and analyzing the data and reports provided by KPP X. The results showed that there were several obstacles in the utilization of AEOI data, especially the accuracy of the data which required adjustments. Utilization of AEOI data effectively increases the participation of HWI Taxpayer in PPS. The tax paid by HWI Taxpayer who has AEOI data is higher than HWI Taxpayer who does not have AEOI data. This success was influenced by several factors, namely synergy and support from colleagues; high tax awareness and ability to pay and concrete power of AEOI data.